Vulnerability Assessment of Spatial Distribution of Filling Station on the Environment in Gombe Metropolis Gombe State Nigeria - Ibrahim, Jimoh A.; Kalak, Joshua I.; Hashidu, Rabiu B.; Inusa, Musa; Adamu, Dahiru (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY (2536-6041), 2025)
The study analyzed the effects of spatial distribution of fuel stations on the environment in Gombe Metropolis, Nigeria. The coordinates of fuel stations were collected and analyzed using ArcGIS 10.1 to determine their spatial distribution and compliance with the Department of Petroleum Resource (DPR) standard. The results of the Nearest Neighbour Analysis showed a strong clustering of filling stations, with a mean distance of 281 meters between filling stations, which is less than the expected mean distance of 593 meters. There is a strong clustering of fuel stations within a distance of 400 meters, with 78 out of 84 fuel stations located within 400 meters of each other. Only 7.14 % of fuel stations are located at a distance greater than 400 meters. The study further indicated that the majority of the fuel stations (71 %) are located within 30 meters of residential areas which poses serious health risks. The clustering of fuel stations and their proximity to residential areas, and road networks can lead to traffic congestion, air pollution, fire hazards, and accessibility issues. The results of the study suggest that policymakers need to ensure that fuel stations conform to safety regulations set by DPR for sustainability.